Unbalance power flow calculation for a radial distribution system using forward-backward propagation algorithm - Ulinuha, A.; Masoum, Mohammed; Islam, Syed (Curtin University of Technoklogy, 2007)
Three-phase power flow for unbalance distribution system is carried out using forward- backward propagation technique. The equivalent injection current method is employed to represent the loads and shunt admittances. The algorithm starts with mapping the distribution network to determine the forward and backward propagation paths. The backward propagation is used to calculate branch currents using the bus injection currents. The forward propagation is employed to calculate bus voltages using the obtained branch currents and line impedances. The algorithm offers robust and good convergence characteristics for radial distribution system. The algorithm is presented for the IEEE 34- bus system. The unbalance level of the system is also analysed.